Building heights: Influence on thermal pedestrian environment and behaviour a case study in Bauru-SP, Brazil - Souza, Léa C.L. (2010)
This paper is an application of a Multi-Agent System technique, carried out for an analysis of the thermal environment of pedestrians in a residential area. A current urban situation was compared to two hypothetical scenarios for the same area. The results show that the promotion of shadows for the climate conditions under analysis could help on the quality of the thermal environment of the pedestrians, particularly during the afternoons.